In lumpfish We Trust? The Efficacy of Lumpfish Cyclopterus lumpus to Control Lepeophtheirus salmonis Infestations on Farmed Atlantic Salmon: A Review - Albert Kjartan Dagbjartarson Imsland; Patrick Reynolds (Fishes, 2022)
In this review, we have systematized current knowledge about the effect of stocking lumpfish (Cyclopterus lumpus) as cleaner fish to control Lepeophtheirus salmonis infestations on farmed Atlantic salmon (Salmo salar L.). The review was prompted by recent reports in which the usefulness of lumpfish has been doubted, and the urgent need to investigate whether common lumpfish can be used to reduce L. salmonis numbers on farmed Atlantic salmon by active grazing on this species. Available published data clearly indicate that lumpfish graze on L. salmonis, and can significantly lower the lice burden in Atlantic salmon farming. It is possible to enhance the lice grazing behavior of lumpfish with the assistance of live feed conditioning prior to sea pen transfer, and with selective breeding. Data indicate that lice grazing of lumpfish is size dependent, and grazing effect is low for lumpfish larger than 200–250 g. Observations from large-scale rearing of Atlantic salmon in open sea cages in Norway, Iceland, the Faroe Islands, and Scotland also indicate that lumpfish can be effective in lowering infestations of L. salmonis on salmon. Overall, this present review reveals that lumpfish can actively contribute to lower numbers of L. salmonis on farmed Atlantic salmon.